Carbon–carbon bond cleavage for Cu-mediated aromatic trifluoromethylations and pentafluoroethylations - Sugiishi, Tsuyuka; Amii, Hideki; Aikawa, Kohsuke; Mikami, Koichi (Beilstein Journal of Organic Chemistry, 2015)
This short review highlights the copper-mediated fluoroalkylation using perfluoroalkylated carboxylic acid derivatives. Carbon–carbon bond cleavage of perfluoroalkylated carboxylic acid derivatives takes place in fluoroalkylation reactions at high temperature (150–200 °C) or under basic conditions to generate fluoroalkyl anion sources for the formation of fluoroalkylcopper species. The fluoroalkylation reactions, which proceed through decarboxylation or tetrahedral intermediates, are useful protocols for the synthesis of fluoroalkylated aromatics.
Keywords: β-carbon elimination; carbon–carbon bond cleavage; decarboxylation; tetrahedral intermediate; trifluoroacetate; fluoral; trifluoromethylation